Determination of surface properties using speckle metrology: case of special papers - Pino, Abdiel; Pladellorens, Josep (IJRDO-Journal of Applied Science, 2017)
We present an experimental approach to measure of the roughness of the paper on the real time based in the analysis of speckle pattern on the surface. The image formed by speckle in the paper surface is considered as a texture, and therefore texture analysis methods are suitable for the characterization of paper surface. The properties statistical of this speckle pattern are used for estimation and quantification of roughness parameter Ra and Rq. We applied digital image processing using statistics of second order, specifically the gray level co-occurrence matrix (GLCM), so this method can be considered as non-contact surface profiling method. The results are contrasted to confocal microscopy, autocorrelation function and fringe projection.